Cylindrical structure for medical application - Wu, Ya Dong. (2010)
In order to solve the major problems of current stents, such as stent migration and stent restenosis, two new types of stent have been proposed in this project, namely origami stent graft and self-expanding braided Nitinol stent. The designs, fabrication processes and properties of new stents have been investigated for the medical application.